The Role of Philosophical Schools in Scientific Research - Nugraha, Diki Egie; Z, Zulfan Zulkarnaen; Winarno, Agung (Formosa Journal of Multidisciplinary Research, 2025)
This study examines the contributions of philosophical streams—positivism, interpretivism, pragmatism, and critical realism—in shaping scientific research paradigms, methods, and ethics. Each philosophical approach has unique characteristics that influence how researchers understand reality, develop theories, and select research methods. Positivism emphasizes objectivity through empirical observation and quantitative analysis to identify causal relationships. In contrast, interpretivism focuses on subjective understanding and social meaning derived from individual experiences, making it suitable for qualitative research. Pragmatism offers a flexible approach by integrating quantitative and qualitative methods to address complex research questions and provide practical benefits. Critical realism bridges objective and subjective approaches by exploring the underlying mechanisms of phenomena. Furthermore, these philosophical approaches provide an ethical foundation to ensure that research is conducted responsibly and meets societal needs. By understanding and applying these philosophical paradigms, researchers can produce more holistic studies and contribute significantly to advancing knowledge.